Corrosion Mechanism of 12Cr2NiWVA Cylinder Liners - Peng, Zhiling; Zhao, Heming (Asian Journal of Chemistry, 2014)
The corrosion mechanism of the inner surface of 12Cr2NiWVA cylinders under high temperature and high pressure conditions has been investigated in this paper. The corrosion and SEM morphology on the inner cylinder surfaces were observed and the effects of nitriding, heat treatments and finish grinding were studied. By analyzing the corrosive ingredients and measuring section hardness, it revealed that the chromium content in the matrix is reduced during the nitride treatment on the inner surface. The oxidation, corrosion and wear resistance is reduced due to grinding on the finish and uneven temperatures during the heat treatment leads to decreased performance and deformation of the product increases.